2016
DOI: 10.1002/adma.201603436
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Stretchable Energy Storage: Recent Advances and Future Perspectives

Abstract: Energy-storage technologies such as lithium-ion batteries and supercapacitors have become fundamental building blocks in modern society. Recently, the emerging direction toward the ever-growing market of flexible and wearable electronics has nourished progress in building multifunctional energy-storage systems that can be bent, folded, crumpled, and stretched while maintaining their electrochemical functions under deformation. Here, recent progress and well-developed strategies in research designed to accompli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
639
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 942 publications
(639 citation statements)
references
References 215 publications
(214 reference statements)
0
639
0
Order By: Relevance
“…To more easily and affordably use the above-mentioned energy sources, energy storage devices must be dramatically improved [1][2][3][4][5]. Rechargeable batteries and supercapacitors are the two most commonly used devices for energy storage, and have attracted persistent research attention over the last few decades [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To more easily and affordably use the above-mentioned energy sources, energy storage devices must be dramatically improved [1][2][3][4][5]. Rechargeable batteries and supercapacitors are the two most commonly used devices for energy storage, and have attracted persistent research attention over the last few decades [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…stretchable energy storage applications. [23,32] Such gel electrolytes can overcome the leakage problem of liquid electrolyte during stretching, and the overall resistance can be reduced by a thinner electrolyte layer. Gilshteyn et al reported that the stretchable transparent supercapacitor with PVA/H 2 SO 4 gel electrolyte showed 2.3-fold higher specific capacitance compared to the device with H 2 SO 4 electrolyte and a nonstretchable separator.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Therefore, new concepts and approaches for stretchable transparent batteries are necessary to address such challenging issues. Recent efforts have demonstrated stretchable [23] or transparent batteries, [31] which can inspire the future development of stretchable transparent batteries. Liu et al reported a stretchable Li 4 Ti 5 O 12 anode and LiFePO 4 cathode using the 3D porous sponge-like PDMS scaffolds.…”
Section: Batteriesmentioning
confidence: 99%
“…However, the encapsulation of liquid electrolytes in wearable ESCDs is challenging, due to potential safety issues such as leakage, flammability, and poor chemical stability while energy devices are being used. [56] Therefore, considerable efforts have been made to replace liquid electrolytes with gel and solid ionic electrolytes.…”
Section: Intrinsically Stretchable Materials For Stretchable Electrolmentioning
confidence: 99%